Marketing Management Plan Infinity Workspace - Rahmat, Didi; Indradewa, Rhian; Abadi, Ferryal; Iskandar, Muhammad Dhafi (Syntax Literate, 2025)
This research aims to develop a model of travel patterns and regular tour packages as an effort to support the development of leading tourist destinations of Bima Bay in Bima City. The Bima Bay area has marine, cultural, and natural tourism potential that has not been fully utilized optimally within the framework of sustainable tourism development. This research uses a qualitative approach with exploratory descriptive methods, supported by SWOT analysis and field observations, as well as in-depth interviews with local tourism stakeholders, including business actors, local governments, and tourism communities. The results of the study show that the development of structured and scheduled regular travel patterns and tour packages can increase tourist visits and extend the length of stay in Bima City. The model developed includes the integration of tourist attractions around Bima Bay, such as Lawata Beach, Kambing Island, to traditional villages and snorkeling spots, which are packaged in the form of daily and weekly packages. In addition, the model considers aspects of sustainability, infrastructure readiness, and local community involvement. The main recommendation of this study is the need for synergy between the government, tourism actors, and the community in the implementation of the proposed model. Strengthening promotions, increasing the capacity of tourism human resources, and improving accessibility and supporting facilities are the keys to the successful development of Bima Bay as a leading tourist destination in the eastern region of Indonesia.